Care bundle for induction of labour of intrauterine fetal death >24/40: completed audit cycle of a UK teaching hospitals' practice before and after rcog green-top guideline implementation. (18th April 2012) - Turnbull, HL; Stanley, K; Harlow, F; Simpson, P
Abstract : Introduction: Various methods of induction of labour (IOL) have been used for intrauterine fetal death (IUFD) at the Norfolk & Norwich University Hospital. The RCOG only published green-top guidance in 2010.1 Previously, IOL management was often reliant on consultant experience and contradicting literature. Historically, management was similar to pregnancy-terminations dosage with the unlicensed prostaglandin-E1-analogue misoprostol (miso), and anti-progesterone, mifepristone (mife). Dangerous misoprostol-dosage was highlighted by Fiala & Weeks' data, which suggested the danger of increased uterine sensitivity in later gestations.2 Method: The 1 st 20-patient audit cycle, studied the safety and efficiency of our IOL of IUFD in comparison with published practice. We implemented a hospital guideline based on Gomez et al (3 ) and RCOG's1 guidance, but with the use of a "care bundle". Three months following implementation, the 2 nd 20-patient audit cycle was done. The care bundle includes 8 essential requirements for IUFD management, including drug-dosage, amniotomy-timing and administrative requirements, with a sticker to be placed in the notes for easier implementation. Conclusion: The 1 st audit cycle highlighted 10 different induction-drug combinations. Only 10 (50%) women had the mife/miso combination, of which 90% received "unsafe" doses according to Fiala et al, 3 highlighting significant safety issues and hyperstimulation-risk. 12/20 management plans were unclear, with 16/20 being poorly followed. The 2 nd audit cycle identified a huge improvement in management, documentation, and plan-implementation. 90% received safe, recommended misoprostol doses. Care Bundles have helped implement changes, and are a useful auditing tool for on-going monitoring, whilst improving patient safety.